A finite element study of adhesion of soft thin elastic films cast on rough surfaces. (December 2017) - Mishra, Satish; Annepu, Hemalatha; Sarkar, Jayati
Abstract: Contact instability of thin elastic films rigidly bonded to patterned substrates, in comparison to those bonded to smooth substrates, were found to form highly miniaturized patterns at their free surfaces. Through finite element simulations, we have found that irrespective of the widely varying substrate patterns used (step, sinusoidal, sawtooth and noisy sinusoidal, with different substrate parameters), the salient miniaturized surface features engendered in these films are found to be same for identical RMS substrate-roughnesses. Columns formed at the film-contactor interfaces of these patterned-substrate films are found to be very slender with larger contact area and are comparatively able to bear very high stresses (responsible for higher peak debonding forces). These columns simultaneously display higher stress release during debonding that leads to almost identical snap-off distances and consequentially, higher work of adhesion is observed. Additionally, work of adhesion also increases for higher debonding velocities. The RMS substrate roughnesses promote these films to perform as potentially better adhesives and, their influence on pattern miniaturization can be harnessed to enhance other surface properties.